Importance of Forensic Science in Crime Investigation - Yogender Singh; Pratima Devi Ranga (Indian Journal of Forensic Medicine & Toxicology, 2021)
Forensic science has been used for justice delivery system since ages. However it started gaining groundin early fifties as an independent discipline and since then it has derived applications from every field ofscience and technology. Today it is well settled and much sought after and ever growing technology forensicsand forensic investigations are fast changing their face as every other day new types of crimes are beingcommitted. To cope up with the demanding nature of this profession, forensic services need up-gradation atevery stage. This paper focuses on the applicability of Forensic science in criminal investigation and the roleit plays in keeping law and order in a society, also throws light on how forensic science is acting as a bridgebetween the medical scientists and legal scientists.